Identifying and classifying quality of life tools for neurogenic bladder function after spinal cord injury: A systematic review. (3rd September 2017) - Best, Krista L.; Ethans, Karen; Craven, B. Catharine; Noreau, Luc; Hitzig, Sander L.
Abstract : Objective : To identify and classify quality of life (QoL) tools for assessing the influence of neurogenic bladder after spinal cord injury/disease (SCI). Design : Systematic Review Methods : Medline/Pubmed, CINAHL, and PsycInfo were searched using terms related to SCI, neurogenic bladder and QoL. Studies that assessed the influence neurogenic bladder on QoL (or related construct) in samples consisting of ≥50% individuals with SCI were included. Two independent reviewers screened titles and abstracts of 368 identified references; 118 full-text articles were assessed for eligibility, and 42 studies were included. Two reviewers independently classified outcomes as objective (societal viewpoint) or subjective (patient perspective) using a QoL framework. Results : Ten objective QoL measures were identified, with the Medical Outcomes Short Form (SF-36/SF-12) used most frequently. Fourteen subjective QoL measures were identified; 8 were specific to neurogenic bladder. Psychometric evidence for SCI-specific neurogenic bladder QoL tools was reported for the Quality of Life Index (QLI), Qualiveen, Bladder Complications Scale, Spinal Cord Injury-Quality of Life (SCI-QOL) Bladder Management Difficulties, and the SCI-QOL Bladder Management Difficulties-Short Form. The QLI and Qualiveen showed sensitivity to neurogenic bladder in experimental designs. Conclusion : Several objective and subjective tools exist to assess the influence of neurogenic bladder on QoL in SCI. The QLI and Qualiveen, both subjective tools, were the only validated SCI-specific tools that showed sensitivity to neurogenic bladder. Further validation of existing subjective SCI-specific outcomes is needed. Research to validate objective measures of QoL would be useful for informing practice and policy related to resource allocation for bladder care post-SCI.